Solvent effects on esterification equilibria. Issue 9 (September 2015) - Riechert, Ole; Husham, Maik; Sadowski, Gabriele; Zeiner, Tim
<x xml:space="preserve">Abstract</x> Solvents are known to have strong impacts on the yields of equilibrium reactions. This work focuses on the thermodynamic investigation of these solvent effects on esterification reactions of acetic acid and propionic acid with ethanol. Esterification of acetic acid was performed in the solvents acetone, acetonitrile (ACN), dimethylformamide (DMF), and tetrahydrofurane as well as in mixtures thereof. ACN promotes the esterification of acetic acid, whereas it is strongly suppressed by DMF. The esterification of propionic acid was investigated with various reactant concentrations in acetone. The experimental equilibrium data in pure solvents and solvent mixtures were modeled using the thermodynamic equilibrium constant Ka and the reactant/product activity coefficients predicted by the perturbed chain‐statistical associating fluid theory (PC‐SAFT). For a given Ka, PC‐SAFT is able to predict the influence of the solvent and even solvent mixtures on the equilibrium concentrations of esterification in almost quantitative agreement with the experimental data. © 2015 American Institute of Chemical Engineers AIChE J, 61: 3000–3011, 2015